2020
DOI: 10.1186/s13229-020-00380-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical health of autistic girls and women: a scoping review

Abstract: Background There is a growing recognition of sex and gender influences in autism. Increasingly, studies include comparisons between sexes or genders, but few have focused on clarifying the characteristics of autistic girls’/women’s physical health. Methods A scoping review was conducted to determine what is currently known about the physical health of autistic girls/women. We screened 1112 unique articles, with 40 studies meeting the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 95 publications
3
24
0
3
Order By: Relevance
“…Compared with autistic men and typically developing women, women with ASD report more often comorbid physical health conditions (e.g., polycystic ovary syndrome, 7.8 vs. 3.5% in the general population) (49) and less utilization of women's health services (OR = 0.59, 95% CI = 0.48-0.72) (50). The barriers to accessing adequate healthcare include providers' lack of knowledge and dedicated training regarding autistic women' needs for care and the lack of specific services for adults with ASD (22,49,50). Although it has been proposed that autistic women's lower access to women's health services could be explained by less frequent sexual experiences (50), several studies have reported the opposite (23,24,34).…”
Section: Access To Adequate Healthcarementioning
confidence: 99%
“…Compared with autistic men and typically developing women, women with ASD report more often comorbid physical health conditions (e.g., polycystic ovary syndrome, 7.8 vs. 3.5% in the general population) (49) and less utilization of women's health services (OR = 0.59, 95% CI = 0.48-0.72) (50). The barriers to accessing adequate healthcare include providers' lack of knowledge and dedicated training regarding autistic women' needs for care and the lack of specific services for adults with ASD (22,49,50). Although it has been proposed that autistic women's lower access to women's health services could be explained by less frequent sexual experiences (50), several studies have reported the opposite (23,24,34).…”
Section: Access To Adequate Healthcarementioning
confidence: 99%
“…Specifically, it is important to raise the awareness of clinicians providing women's health care (e.g. primary care physicians, obstetricians, and gynecologists) of the care needs of their autistic patients (Kassee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that such interventions lead to better reproductive, maternal, and neonatal outcomes, including improved fertility and lower rates of pregnancy complications, preterm birth, congenital anomalies, and maternal and neonatal mortality (H. K. World Health Organization, 2012). While we know little about autistic women's pregnancy outcomes and experiences, recent research suggests that they are at increased risk of medical and psychiatric complications (Gardner et al, 2016;Kassee et al, 2020;Pohl et al, 2020;Rogers et al, 2017;Sundelin et al, 2018). Understanding the health profiles of reproductive-aged autistic women is a prerequisite for improving their perinatal care and preventing adverse maternal and neonatal outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature also suggests increased endocrine and reproductive health conditions in autistic girls/women compared to non-autistic girls/women. However, the findings regarding gastrointestinal, metabolic, nutritional, and immune-related conditions are preliminary and inconsistent [20].…”
Section: Discussionmentioning
confidence: 99%